Réponses

2013-10-05T14:02:42+02:00
(X + 3)² = X² + 2 x 3 x X + 3² = X² + 6X + 9
Il faut faire la même chose pour les autres
(X-7)² = X² - 2 x 7 x X + 7² = X² - 14X + 49
idem pour les autres
(x+3)(x-3)= x² - 9   C'est le premier au carré - le 2ème au carré.
(3x+5)(3x-5) = 9x² - 25
  • Utilisateur Brainly
2013-10-05T14:04:08+02:00
(x+3)²=x²+6x+9
(5+x)²=25+10x+x²
(3x+4)²=9x²+24x+16

(x-7)²=x²-14x+49
(2x-3)²=4x²-24x+9
(5-4x)²=25-40x+16x²

(x+3)(x-3)=x²-9
(3x+5)(3x-5)=9x²-25
(2-7x)(2-7x)=4-49x²
(2x-9)(2x+9)=4x²-81